Сенсори ультрафіолетового випромінювання на основі твердих розчинів ZnxCd1 – xS - Pavelets, S. Yu.; Bobrenko, Yu. N.; Semikina, T. V.; Atdaev, B. S.; Sheremetova, G. I.; Yaroshenko, M. V. (Publishing house "Academperiodika", 2019)
Effective semiconductor ultraviolet sensors on the basis of Zn0.6Cd0.4S and Zn0.7Cd0.3 solid solutions (SSs) are fabricated. The sensors include variband layers and a thin (∼10 nm) stable polycrystalline p-Cu1.8S film as a transparent component of the surface-barrier structure. The n-CdS layers are used as substrates for the epitaxial growing of SSs. The problems of obtaining low-resistive ZnxCd1−xS polycrystalline layers, providing an ohmic contact with them, and matching the lattice parameters in the SS and the substrate material are resolved by applying intermediate variband layers. On the basis of a heterostructure with glass filters, a selective sensor in the UV-A spectral interval is developed, as well as sensors sensitive to the pigmentation interval of solar radiation (the violet-blue section). Energy band diagrams of the multilayer structure are plotted. The results of Auger-spectroscopic researches and the researches of the main electrical and photovoltaic properties of sensors are reported.